2012
DOI: 10.1016/s1734-1140(12)70940-4
|View full text |Cite
|
Sign up to set email alerts
|

Level of S100B protein, neuron specific enolase, orexin A, adiponectin and insulin-like growth factor in serum of pediatric patients suffering from sleep disorders with or without epilepsy

Abstract: Out of the five putative biomarkers measured, blood concentration of S100B and orexin A may be helpful in differentiating parasomnic pediatric patients with and without epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
4
24
0
2
Order By: Relevance
“…Before starting the second IGF1 administration, the crisis had a daily frequency and they remained unaltered during the whole cycle of treatment. These observations are in accordance to the literature in pediatric syndromes, where IGF1 is not associated to an increase in seizures, but rather epileptic phenotype is associated to decreased IGF1 levels in the serum (14, 15). On the contrary, it is possible that the seizure medication hindered the positive effects of IGF1.…”
Section: Discussionsupporting
confidence: 92%
“…Before starting the second IGF1 administration, the crisis had a daily frequency and they remained unaltered during the whole cycle of treatment. These observations are in accordance to the literature in pediatric syndromes, where IGF1 is not associated to an increase in seizures, but rather epileptic phenotype is associated to decreased IGF1 levels in the serum (14, 15). On the contrary, it is possible that the seizure medication hindered the positive effects of IGF1.…”
Section: Discussionsupporting
confidence: 92%
“…Serum neurotropic protein S100B, secreted and synthesized by oligodendrocyte and astroglia, is a sensitive indicator of brain injury [43]. Pathological changes, such as proliferation of gliocytes, damage of blood brain barrier, demyelinating of central nerves, and neuron injury that take place in the brain after epileptic seizure, lead to increased S100B protein [44,45]. In the current study, we showed that levetiracetam treatment lowered S100B protein levels in patients with refractory epilepsy (P \ 0.05).…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, as Kcna1 À/À mice approach SD, basal respiratory drive and peak inspiratory flow are uniquely increased. 39,40 Elevation of orexin may be a compensatory mechanism to increase respiratory drive in people with respiratory failure. Increased peak inspiratory flow indicates deeper inspiration.…”
Section: Mch Paradoxically Provokesmentioning
confidence: 99%